(untitled) (Tạp chí Nghiên cứu Khoa học Công đoàn, 2020)
The industrial revolution 4.0 is taking place every day, every hour for all countries in the world including Vietnam. However, each country has different economic - cultural - social characteristics, natural geographic conditions; therefore, in order to go short and be proactive to develop rapidly, countries need to grasp opportunities and challenges. Vietnam has a country of more than 700,000 enterprises, of which about 95% of small and medium enterprises, need to understand the opportunities, and know the challenges to cope and integrate in the current context.